Assessment of the control measures of the category A diseases of Animal Health Law: Burkholderia mallei (Glanders). (12th January 2022) - ,; Nielsen, Søren Saxmose; Alvarez, Julio; Bicout, Dominique Joseph; Calistri, Paolo; Canali, Elisabetta; Drewe, Julian Ashley; Garin‐Bastuji, Bruno; Gonzales Rojas, José Luis; Schmidt, Christian Gortázar; Herskin, Mette; Michel, Virginie; et al.
Abstract: EFSA received a mandate from the European Commission to assess the effectiveness of some of the control measures against diseases included in the Category A list according to Regulation (EU) 2016/429 on transmissible animal diseases ('Animal Health Law'). This opinion belongs to a series of opinions where these control measures will be assessed, with this opinion covering the assessment of control measures for glanders. In this opinion, EFSA and the AHAW Panel of experts review the effectiveness of: (i) clinical and laboratory sampling procedures, (ii) monitoring period and (iii) the minimum radius of the protection and surveillance zone, and the minimum length of time the measures should be applied in these zones. The general methodology used for this series of opinions has been published elsewhere. Considering the epidemiology and distribution of glanders, it was foreseen that three different situations could lead to a suspicion of the disease. Sampling procedures were defined for each of the three different suspicion types, which can also be applied in most of the other scenarios assessed. The monitoring period (6 months) was assessed as effective in all scenarios. The AHAW Panel of experts considered the minimum radius and duration of the existing protection and surveillance zone, set at the establishment level, effective. Recommendations provided for each of the scenarios assessed aim to support the European Commission in the drafting of further pieces of legislation, as well as for plausible ad hoc requests in relation to glanders.